Panton-Valentine Leukocidin and concurrent respiratory viral infection as risk factors for fatal Staphylococcus aureus bacteremia - Zhou, Liting; Guo, Shiqi; Zhang, Ting; Bi, Ruru; Han, Qingzhen; Guo, Qiang (Frontiers in Microbiology, 2026)
BackgroundStaphylococcus aureus bacteremia (SAB) carries significant mortality. We sought to define clinical and pathogen-specific risk factors to guide early intervention.MethodsWe conducted a retrospective cohort study of all SAB cases at our institution (Jan 2021–Mar 2025), expanding from an initial analysis of four fatal cases. Patient profiles, clinical characteristics and microbiological features were analyzed. Independent risk factors for mortality were determined through multivariate logistic regression.ResultsAmong 40 patients, mortality was higher in the community-associated Staphylococcus aureus (CASA) group (38.5% vs. 14.3%). Analysis revealed Panton-Valentine Leukocidin (PVL)-positive, methicillin-susceptible ST22 strains caused fatal outcomes in patients co-infected with influenza A or SARS-CoV-2, accompanied by severe leukopenia. Multivariate analysis identified fever before admission, PVL-positive S. aureus with respiratory viral co-infection, and ST22 strain infection as independent mortality risk factors. In the CASA subgroup, diabetes and PVL with viral co-infection were significant predictors.ConclusionPVL-producing strains, especially ST22, are key mortality drivers in SAB, with effects amplified by respiratory viral co-infection. Early recognition of PVL/viral co-infection and comorbidity management are critical for improving outcomes.